A Simulation-Driven Study of Bottleneck Reduction in Crude Palm Oil Production Using Arena Software - Tee, Bing Hong Anthony; Selimin, Mohamad Ali; Abdul Hamid, Nor Aziati (Research in Management of Technology and Business, 2026)
Productivity is determined by output within the production process and is achieved through a combination of effectiveness, doing the right things, and efficiency, doing things correctly. In the context of the issues faced, bottlenecks impact productivity primarily due to two factors: worker scheduling and the method used to identify the bottleneck. The objectives of this study are to determine the root cause of bottlenecks related to worker schedules, identify other critical bottlenecks using Arena simulation, and propose solutions to address these constraints. Arena simulation was employed due to its cost-effectiveness compared to alternative methods. Production data were collected through interviews, direct observation and time study. Key findings revealed that improper worker allocation led to delays in critical processes, notably the deliver to oil room process. Simulation results showed that optimising worker schedules and increasing resource capacity effectively reduced production cycle times. This study highlights the value of simulation tools as a cost-efficient approach for identifying and resolving bottlenecks, ultimately supporting enhanced productivity within manufacturing systems.